The serum sclerostin level is positively associated with the aortic augmentation index in patients on peritoneal dialysis - Lin, Lin (Tzu Chi Med J, 2019)
OBJECTIVE: Sclerostin is a canonical Wingless (Wnt)/β-catenin signaling pathway inhibitor and had been associated with high arterial stiffness in patients with chronic kidney disease. The aortic augmentation index (AIx), a noninvasive method of assessing central hemodynamics/wave reflections, has been widely used as a clinical index of arterial stiffness. The aim of this study was to evaluate the relationship between fasting serum sclerostin levels and AIx values in peritoneal dialysis (PD) patients. MATERIALS AND METHODS: Fasting blood samples were obtained from 75 PD patients. The aortic AIx value was measured using a validated tonometry system (SphygmoCor, AtCor Medical, Sydney, New South Wales, Australia). Serum sclerostin and dickkopf-1 (DKK1) levels were quantified using commercial enzyme-linked immunosorbent assay kits. RESULTS: Women PD patients had higher aortic AIx values than men (P = 0.039), while lower aortic AIx values were found in PD patients who used statins (P = 0.004). Univariate linear analysis of the aortic AIx values in PD patients showed that systolic blood pressure (P = 0.001), diastolic blood pressure (P = 0.018), and serum sclerostin levels (P = 0.001) were positively correlated, while height (P = 0.018), body weight (P = 0.001), body mass index (P = 0.043), and weekly total creatinine clearance (P = 0.015) were negatively correlated with aortic AIx values in PD patients. Multivariate linear regression analysis of the factors significantly associated with the aortic AIx values showed that serum sclerostin levels (adjusted R(2) = 0.057, P = 0.011) and systolic blood pressure (adjusted R(2) = 0.125, P = 0.004) were positively associated, while body weight (adjusted R(2) = 0.113, P = 0.002) was inversely associated with aortic AIx values in PD patients. CONCLUSION: In this study, the serum sclerostin level, but not DKK1, was positively associated with aortic AIx values in PD patients.